The “Boko Haram Disaggregation Problem” and Comparative Profiles of Factional Violence: Challenges, Impacts, and Solutions in the Study of Africa’s Deadliest Terror Group(s) - Warner, Jason (Terrorism and political violence, 2023)
This article introduces the “Boko Haram disaggregation problem,” or the often frequent failure by observers to disaggregate the group following its August 2016 split into two distinct factions, instead, labeling and studying all factions as “Boko Haram.” It asks: What are the origins of the “Boko Haram disaggregation problem,” and, given this phenomenon, what are the possibilities and constraints in understanding profiles of violence between the pre-2016 and post-2016 iterations of the group(s)? It argues that the “Boko Haram disaggregation problem” has origins both internal and external to the group(s), most prevalent in quantitative academic research. Highlighting the challenges of this phenomenon, it uses data from the Global Terrorism Database (GTD) from 2009 to 2018 to compare profiles of violence between various “Boko Haram” factions. In sum, it shows why beyond merely a methodological challenge, overcoming this phenomenon has real-world impacts for addressing the violence perpetrated by these groups.